Sepsis Early Alert Tool: Early recognition and timely management in the emergency department. (5th May 2016) - Idrees, Marwan; Macdonald, Stephen PJ; Kodali, Kiren
Abstract: Introduction: The Surviving Sepsis Campaign guidelines recommend administration of appropriate antibiotics within 1 h in patients with severe sepsis, with two sets of blood cultures taken prior to administration. Objective: We evaluated the effect of introducing a Sepsis Early Alert Tool (SEAT) in the ED. Outcomes were antibiotic timing, antibiotic choice and obtaining adequate blood cultures. Methods: A retrospective chart review compared consecutive severe sepsis presentations admitted to ICU via the ED during two equivalent 6 month periods before and after SEAT introduction. Results: The analyses included 55 patients before and 45 following SEAT introduction. The groups were similar in age, sex, triage category, sepsis source, Acute Physiology and Chronic Health Evaluation III scores and hospital mortality. The percentage receiving antibiotics within 60 min of triage increased from 24% (95% CI 13–37%) to 44% (95% CI 30–60%), P  = 0.03. Median time from triage to first antibiotic was 105 (IQR 65–170) min and 85 (IQR 50–140) min before and after SEAT introduction, respectively, P  = 0.15. Percentages receiving antibiotics within 60 min of first recognition of severe sepsis were 67% (95% CI 53–79%) and 71% (95% CI 56–84%) before and after SEAT introduction, P  = 0.83. The percentage having two sets of blood cultures drawn prior to antibiotic administration increased from 18% (95% CI 9–34%) to 44% (95% CI 27–60%), P  = 0.008. Appropriateness of antibiotics was 58% (95% CI 44–71%) and 75% (95% CI 60–87%) before and after SEAT implementation, P  = 0.09. Conclusion: The introduction of a SEAT in the ED is associated with earlier recognition of severe sepsis and improvements in quality of care.